ANALISIS HUBUNGAN PENYALURAN KREDIT DENGAN TINGKAT LIKUIDITAS PADA BANK YANG TERDAFTAR DI BEI - Haeril, Haeril; Albar, Albar; Makmur, Maryam (Paser Institute Of Accounting and Finance, 2023)
The purpose of this research was to analyze the influence of the number of loans and the level of liquidity. The Hypotesis in this research is there influence of the number of loans and the level of liquidity. Data that used in this research is secondary data. Data have been collected from Indonesian Stock Exchange and Indonesian Banking at 2013-2015. The sample in this research is ten of the company banks that listed in Indonesian Stock Exchange. The analisys that used is multiple regressions, clasic asumption, R2. The result of the test show that influence of the number of loans and the level of liquidity have negative influence toward stock price. The R2 show as 0.194 it means that independent variable can explain 19.4 % of dependent variable and 80.6 % can be explained by another variabel.